Synthesis and Preliminary Pharmacological Study of Sulfonamide Conjugates with Ibuprofen and Indomethacin as New Anti-Inflammatory Agents - Bader S. Salem; Monther F. Mahdi; Mohammed H. Mohammed (College of Pharmacy University of Baghdad, 2017)
4-aminobenzenesulfonamide conjugates of ibuprofen (compound 10) and indomethacin (compound 11) have been designed and synthesized by the reaction of sulfanilamide (compound 7) with 2-(4-isobutylphenyl) propanoic acid (ibuprofen) and 2-(1-(4-chlorobenzoyl)-5-methoxy-2-methyl-1H-indol-3-yl)acetic acid (indomethacin) for the evaluation as potential anti-inflammatory agents with expected selectivity against COX-2 enzyme. In vivo acute anti-inflammatory activity of the synthesized final compounds (10 and 11) was evaluated in rats using egg-white induced edema model of inflammation in a dose equivalent to (10mg/Kg) of ibuprofen and (2mg/kg) of indomethacin. The tested compounds produced significant reduction of the rat paw edema with respect to the effect of propylene glycol 50% v/v (control group). Moreover, compound (10) exhibited comparable anti-inflammatory activity to diclofenac (3mg/Kg) (reference group) while compound (11) exhibited less anti-inflammatory activity than diclofenac. The result of this study indicate that the incorporation of the 4-aminobenzenesulfonamide pharmacophore into ibuprofen and indomethacin maintained their anti-inflammatory activity & may increase their selectivity toward COX-2 enzyme which can be confirmed in future by assessing COX-2:COX-1 inhibitory ratio. Key words: Cyclooxygenase; Anti-inflammatory activity; Ibuprofen; indomethacin; NSAIDs.